Navigating the landscape of CEFR-CLIL-based language pedagogy in the Thai context: a captivating journey through needs analysis - Kritpipat Kaewkamnerd; Jarunee Dibyamandala; Charin Mangkhang; Sasinee Khuankaew (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Common European Framework for Languages (CEFR) is a more comprehensive approach to determining international standards. It is essential to note that the CEFR is more than just an assessment since it emphasises the processes of learning, teaching, and assessment. CEFR has recently been recognised nationally in Thailand for designing and developing school curriculums, facilitating teaching and learning, and choosing teaching material. Through a quantitative survey method, this study conducted a needs analysis to investigate the understanding and requirements of 20 senior high school English teachers and 850 learners from selected schools in Chiang Mai regarding the CEFR-CLIL-based curriculum contents in English Language Teaching (ELT). The research utilised a structured questionnaire to gauge the depth of teachers’ and learners’ understanding of the CEFR and ascertain their needs to enhance English competencies within the CEFR-CLIL framework. Findings from this extensive sample highlighted a more profound comprehension and specific needs necessary for designing a CEFR-CLIL-based course adapted to the Thai context. These insights from teachers and learners demonstrated the need for a more integrated approach to English instruction. By shedding light on the specific needs and understandings, the results offered educators an outline for refining ELT strategies, formulating relevant unit topics, and implementing pedagogical techniques in tune with the aspirations of Thai learners, ensuring alignment with the foundational principles of the CEFR guidelines.